Epigenetic alterations underlying autoimmune diseases. (17th February 2016) - Aslani, Saeed; Mahmoudi, Mahdi; Karami, Jafar; Jamshidi, Ahmad Reza; Malekshahi, Zahra; Nicknam, Mohammad Hossein
Abstract: Recent breakthroughs in genetic explorations have extended our understanding through discovery of genetic patterns subjected to autoimmune diseases (AID). Genetics, on the contrary, has not answered all the conundrums to describe a comprehensive explanation of causal mechanisms of disease etiopathology with regard to the function of environment, sex, or aging. The other side of the coin, epigenetics which is defined by gene manifestation modification without DNA sequence alteration, reportedly has come in to provide new insights towards disease apprehension through bridging the genetics and environmental factors. New investigations in genetic and environmental contributing factors for autoimmunity provide new explanation whereby the interactions between genetic elements and epigenetic modifications signed by environmental agents may be responsible for autoimmune disease initiation and perpetuation. It is aimed through this article to review recent progress attempting to reveal how epigenetics associates with the pathogenesis of autoimmune diseases.